2022
DOI: 10.3389/fmicb.2022.896190
|View full text |Cite
|
Sign up to set email alerts
|

Synechocystis sp. PCC 6803 Requires the Bidirectional Hydrogenase to Metabolize Glucose and Arginine Under Oxic Conditions

Abstract: The cyanobacterium Synechocystis sp.PCC 6803 possesses a bidirectional NiFe-hydrogenase, HoxEFUYH. It functions to produce hydrogen under dark, fermentative conditions and photoproduces hydrogen when dark-adapted cells are illuminated. Unexpectedly, we found that the deletion of the large subunit of the hydrogenase (HoxH) in Synechocystis leads to an inability to grow on arginine and glucose under continuous light in the presence of oxygen. This is surprising, as the hydrogenase is an oxygen-sensitive enzyme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…6 b). Synechocystis 6803 produces and accumulates cyanophycin, resulting in increased intracellular arginine levels in BG-11 medium supplemented with 5 mM arginine and 10 mM glucose (Burgstaller et al 2022 ). In this study, the intracellular arginine of these strains with 5 mM arginine was higher than those with 5 mM NaNO 3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 b). Synechocystis 6803 produces and accumulates cyanophycin, resulting in increased intracellular arginine levels in BG-11 medium supplemented with 5 mM arginine and 10 mM glucose (Burgstaller et al 2022 ). In this study, the intracellular arginine of these strains with 5 mM arginine was higher than those with 5 mM NaNO 3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanophycin contains equal molecules of arginine and aspartate, therefore the concentration of cyanophycin equals the amount of arginine. We performed cyanophycin extraction and arginine quantification using the Sakaguchi reaction according to the studies (Burgstaller et al 2022, Messineo 1966) with some modifications. After 3 days of cultivation, Synechocystis 6803 cells [OD 730 × culture volume (mL) = 25] were harvested by centrifugation [5800 × g for 4 min at 25 °C] and 1 mL acetone was added to the cells and incubation with shaking for 30 min.…”
Section: Extraction Cyanophycin and Arginine Quantificationmentioning
confidence: 99%
“…PFOR works coordinatedly with hydrogenase to reduce ferredoxin, which hydrogenase uses as an electron donor (7, 10). Despite their O 2 sensitivity, hydrogenase and PFOR work under mixotrophic (i.e., aerobic) conditions (11, 12). Therefore, uncontrolled expression of hox operon and nifJ may hamper metabolism under photosynthetic conditions or shorten the supply of inorganic cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydrogenase and PFOR are O2 sensitive, they can work under aerobic conditions (10)(11)(12). Therefore, uncontrolled expression of hox operon and nifJ (coding gene of PFOR) may hamper metabolism under photosynthetic conditions.…”
mentioning
confidence: 99%
“…It has long been known that this type of hydrogenase is responsible for hydrogen evolution in the light (so-called photoH 2 ) that is produced when dark anaerobic cells are suddenly exposed to strong light [17]. Recently, we showed that the enzyme is also working as an electron valve when the cells are shifted to high light intensities under aerobic conditions [18]. It remains unclear how the enzyme performs this task but NADH formation from reduced ferredoxin and its subsequent oxidation in respiration are a possible route.…”
Section: Introductionmentioning
confidence: 99%